2023
DOI: 10.1038/s41598-023-38379-0
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus coagulans MZY531 alleviates intestinal mucosal injury in immunosuppressive mice via modulating intestinal barrier, inflammatory response, and gut microbiota

Abstract: Bacillus coagulans has a potential role in improving intestinal injury. However, the specific mechanism is still unclear. In this study, the protective effect of B. coagulans MZY531 on intestinal mucosa injury in cyclophosphamide (CYP)-induced immunosuppressed mice were investigated. The results indicated that the immune organ (thymus and spleen) indices of B. coagulans MZY531 treatment groups were significantly increased compared to the CYP group. B. coagulans MZY531 administration promotes the expression of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…CTX is widely used in treating various cancer and allergic diseases; however, it can damage the immune system, induce disruption of the gut microbiota, and increase the risk of immunodeficiency and intestinal injury diseases, which ultimately can cause adverse effects on the immune system; therefore, CTX is also used in the establishment of immunosuppressed models. 29–31 As important immune organs, the spleen and thymus play crucial roles in regulating immune function. Consistent with the investigations of other researchers, 32–34 our current research indicated that CTX could decrease the body weight, spleen weight, and thymus weight in BALB/c mice, which indicated that CTX could cause damage to the immune system in the mice; however, the supplementation of BC encapsulated by liposomes improved these adverse alterations and exhibited a better effect than BC alone (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…CTX is widely used in treating various cancer and allergic diseases; however, it can damage the immune system, induce disruption of the gut microbiota, and increase the risk of immunodeficiency and intestinal injury diseases, which ultimately can cause adverse effects on the immune system; therefore, CTX is also used in the establishment of immunosuppressed models. 29–31 As important immune organs, the spleen and thymus play crucial roles in regulating immune function. Consistent with the investigations of other researchers, 32–34 our current research indicated that CTX could decrease the body weight, spleen weight, and thymus weight in BALB/c mice, which indicated that CTX could cause damage to the immune system in the mice; however, the supplementation of BC encapsulated by liposomes improved these adverse alterations and exhibited a better effect than BC alone (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…These findings align with previous reports of W. coagulans strains colonizing the intestinal mucosa, whereby they enhance mucosal barrier function, modulate the mucosal immune system, reduce inflammatory factor production, alleviate intestinal inflammation and inflammation-related diseases, promote secretory IgA production, and facilitate antigen-specific immune responses. 41 …”
Section: Discussionmentioning
confidence: 99%
“…This process not only optimizes the structure of the microbial community but also enhances the host’s absorption and utilization of inorganic trace elements through the formation of organic mineral salts. H. coagulans also secretes specialized adhesion proteins, including mucins and fibrinogen-binding proteins, which facilitate colonization in the gut and reduce pathogenic adhesion ( Zhao et al., 2023 ).…”
Section: Probiotic Heyndrickxia Coagulans : Genomi...mentioning
confidence: 99%